Nitrate and Nitrite Promote Formation of Tobacco-Specific Nitrosamines via Nitrogen Oxides Intermediates during Postcured Storage under Warm Temperature - Jun Wang; Huijuan Yang; Hongzhi Shi; Jun Zhou; Ruoshi Bai; Mengyue Zhang; Tong Jin (Journal of Chemistry)
Tobacco-specific nitrosamines (TSNAs) are carcinogenic and are present in cured tobacco leaves. This study was designed to elucidate the mechanisms of TSNAs formation under warm temperature storage conditions. Results showed that nitrogen oxides (NOx) were produced from nitrate and nitrite in a short period of time under 45°C and then reacted with alkaloids to form TSNAs. Nitrite was more effective than nitrate in promoting TSNAs formation during 45°C storage which may be due to the fact that nitrite can produce a large amount of NOx in comparison with nitrate. Presence of activated carbon effectively inhibited the TSNAs formation because of the adsorption of NOx on the activated carbon. The results indicated that TSNAs are derived from a gas/solid phase nitrosation reaction between NOx and alkaloids. Nitrate and nitrite are major contributors to the formation of TSNAs during warm temperature storage of tobacco.